Control and protection of a microgrid connected to utility through back-to-back converters - Majumder, R.; Dewadasa, M.; Ghosh, Arindam; Ledwich, G.; zare, F. (Elsevier S.A., 2011)
This paper discusses the control and protection of a microgrid that is connected to utility through backto-back converters. The back-to-back converter connection facilitates bidirectional power flow between the utility and the microgrid. These converters can operate in two different modes–one in which a fixed amount of power is drawn from the utility and the other in which the microgrid power shortfall is supplied by the utility. In the case of a fault in the utility or microgrid side, the protection system should act not only to clear the fault but also to block the back-to-back converters such that its dc bus voltage does not fall during fault. Furthermore, a converter internal mechanism prevents it from supplying high current during a fault and this complicates the operation of a protection system. To overcome this, an admittance based relay scheme is proposed, which has an inverse time characteristic based on measured admittance of the line. The proposed protection and control schemes are able to ensure reliable operation of the microgrid.